TEMPERATURA E UMIDADE RELATIVA DO AR NA ESTAÇÃO SECA EM DIFERENTES USOS DO SOLO NO CAMPUS CUIABÁ - BELA VISTA DO IFMT - Machado, Nadja Gomes; Friedlander, Victor Amadeo; Sanches, Luciana; Biudes, Marcelo Sacardi (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707706 Cuiabá, known as "Green City" by extensive cerrado fragments present in the urban area,has undergone an accelerated real estate activity without guarantees for the preservation of greenareas. Thus, the objective was to monitor the temporal and spatial variations of temperature andrelative humidity in the different uses and occupation in the Campus Cuiabá - Bela Vista. Thevegetation cover had the lowest air temperature and the highest values of relative humidity, whileareas without vegetation had an another pattern, that is higher values of air temperature andlower values of relative humidity.